Chromosome 1 instability in multiple myeloma: Aberrant gene expression, pathogenesis, and potential therapeutic target. Issue 6 (17th May 2022) - Luo, Saiqun; Su, Tao; Zhou, Xiang; Hu, Wei‐Xin; Hu, Jingping
Abstract: Multiple myeloma (MM), the terminally differentiated B cells malignancy, is widely considered to be incurable since many patients have either developed drug resistance or experienced an eventual relapse. To develop precise and efficient therapeutic strategies, we must understand the pathogenesis of MM. Thus, unveiling the driver events of MM and its further clonal evolution will help us understand this complicated disease. Chromosome 1 instabilities are the most common genomic alterations that participate in MM pathogenesis, and these aberrations of chromosome 1 mainly include copy number variations and structural changes. The chromosome 1q gains/amplifications and 1p deletions are the most frequent structural changes of chromosomes in MM. In this review, we intend to focus on the genes that are affected by chromosome 1 instability: some tumor suppressors were lost or down regulated in 1p deletions, and others that contributed to tumorigenesis were upregulated in 1q gains/amplifications. We have summarized their biological function as well as their roles in the MM pathogenesis, hoping to uncover potential novel therapeutical targets and promote the development of future therapeutic approaches.